A case of puerperal cerebral venous thrombosis - Abhishek Konnur; Gurukanth Rao; Jayaprakash Belle (Wolters Kluwer Medknow Publications, 2024)
Cerebral venous thrombosis (CVT) is a relatively rare, potentially fatal neurological condition that can be frequently overlooked due to the vague nature of its clinical and radiological presentation, particularly when not associated with pregnancy and puerperium. It is a multifactorial disease, and the major forms of clinical presentation include isolated intracranial hypertension syndrome, focal neurological deficits, seizures, and altered sensorium. Magnetic resonance imaging with magnetic resonance venogram is considered the gold standard for diagnosis. Pregnancy-induced changes in coagulation result in a hypercoagulable state, which may naturally reduce the incidence of postpartum hemorrhage but may also increase the risk of CVT. Favorable outcomes have been reported in patients who receive early diagnosis and treatment.